Karakterisasi Morfologis dan Mikroskopis Kapang Pada Roti yang Dijual di Sekitar Kampus Poltekkes Kesuma Bangsa - Sally Khoirunisa (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Bread is a widely consumed food product that is highly susceptible to fungal contamination due to its high moisture and carbohydrate content. Fungal growth on bread can cause deterioration in quality and may pose health risks through the production of mycotoxins. This study aimed to identify and characterize fungi contaminating bread sold around the Poltekkes Kesuma Bangsa campus based on macroscopic and microscopic observations. This research employed a descriptive method and was conducted at the Chemistry Laboratory of Poltekkes Kesuma Bangsa on December 10, 2025. Bread samples were collected using purposive sampling and examined for fungal contamination through macroscopic observation of colony characteristics and microscopic identification using lactophenol cotton blue staining. The results showed that two types of fungi were identified, namely Aspergillus sp. and Penicillium sp. Aspergillus sp. was characterized by white to greenish colonies with a cotton-like surface and spherical vesicles microscopically, while Penicillium sp. exhibited white colonies with granular and slimy surfaces and brush-like conidiophores. One bread sample showed no fungal growth, possibly due to airtight packaging and preservative content. These findings indicate that bread sold around the campus may be contaminated by potentially harmful fungi, highlighting the importance of proper storage and food safety awareness among consumers.